PENGARUH KURMA DALAM MENINGKATKAN KADAR HAEMOGLOBIN PADA IBU HAMIL DI KLINIK PRATAMA HIDAYAH SUKOHARJO - Kamidah; Enny Yuliaswati; Rita Riyanti Kusuma Dewi (Stikes Muhammadiyah Klaten, 2023)
The government has long been trying to overcome anemia in pregnant women by providing 90 tablets of iron supplements which must be consumed during pregnancy. Until now, these efforts have not completely resolved the problem of anemia in pregnant women. According to WHO, the maternal mortality rate associated with anemia is 40%. Low hemoglobin levels in pregnant women can cause non-optimal fetal growth, abortion, prolonged labor, and postpartum hemorrhage. Research Objectives: To determine the effect of dates on increasing hemoglobin levels in pregnant women. Research Method: an intervention study with the one group pre test- post test method. The population of pregnant women with a total sample of 16. Data analysis using the Wilcoxon test. Results: Of the 16 respondents, the average hemoglobin level before being given dates was 10.1 gr/dl and after being given dates, the average hemoglobin level was 11.1 gr/dl. There was an increase in hemoglobin levels of 1 gr/dl after the respondents were given dates. p-value 0.031. Conclusion: There is a significant effect, dates can increase hemoglobin levels.